Iosif Brodsky’s Anapestic Dimeter: Rhythm and Semantics - Barash, Olga (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2021)
The paper discusses the poems by Iosif Brodsky written in cross-rhymed anapestic dimeter with alternating feminine and masculine line endings. The focus is on two poems titled “Strofy” (1968 and 1978). Anapestic dimeter is not typical of Brodsky’s work, his oeuvre includes only four poems written in this meter: “Stansy” (Stanzas, 1962), “Pod zanaves” (At Curtain-Call, 1965) and the two texts with the same title “Strofy” (Strophes, 1968 and 1978). Therefore, an assumption is made that the poet chooses it not by chance and that when doing so he follows the rhythmic patterns and semantic characteristics already established in Russian poetry in connection with this meter. Anapestic dimeter is rarely encountered in Russian poetry, with the main period of its development being the twentieth century, and the set of texts written in this meter limited, which makes it possible to clearly outline the range of possible “metrical pre-texts” of Brodsky’s poems. The metrical and rhythmic characteristics of anapestic dimeter of Brodsky are analysed and compared with those of Boris Pasternak and, on a smaller scale, those of Anna Akhmatova and Innokenty Annensky. The analysis of the poem “Strofy” (1978) shows how Brodsky makes a new use of the metrical-rhythmic potential contained in a seven- or six-syllable speech segment by combining two-word lines of anapestic dimeter with three-word (and therefore three-beat) tonic verses – at the same time retaining the connection both with his predecessors (here, Pasternak) and with his own texts, written earlier or over the same period.